PEDAGOGICAL FEATURES OF CONDUCTING PHYSICAL EDUCATION CLASSES IN EDUCATIONAL INSTITUTIONS - Kholova Shakhnoza Mardonovna; Isroilova Zebiniso Mamadiyarovna (JOURNAL OF NEW CENTURY INNOVATIONS, 2025)
Abstract: This article discusses the pedagogical foundations for effectively organizing physical education classes in educational institutions. It emphasizes the need to consider students’ physical conditions, the use of modern equipment, and methodological approaches. Through pedagogical sources, the article analyzes the role of physical education in promoting a healthy lifestyle, enhancing social activity, and serving as methodological support in the educational process.